1999
DOI: 10.1557/proc-603-137
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Pyrochlore Films for Dielectric Applications

Abstract: Bismuth pyrochlore ceramics have modest temperature coefficients of capacitance, good microwave properties, and can be prepared at relatively modest temperatures (∼900 – 1100 °C). This work focuses on the preparation and characterization of thin films in this family for the first time. A sol-gel procedure using bismuth acetate in acetic acid and pyridine, in combination with zinc acetate dihydrate and niobium ethoxide in 2-methoxyethanol was developed. The solution chemistry was adjusted to prepare (Bi1.5Zn0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…2 and 3͔͒. 12,13 No dielectric relaxation was observed in monoclinic BZN, 14 which corresponds also to a better ordered crystal structure. [4][5][6][7] In cubic pyrochlore BZN the Bi and Zn atoms in the A positions are disordered among six closely spaced equivalent sites and the OЈ atoms from the A 2 OЈ tetrahedral network among 12 sites, 4 while the Zn atoms prefer the B site to the A site.…”
Section: Introductionmentioning
confidence: 96%
“…2 and 3͔͒. 12,13 No dielectric relaxation was observed in monoclinic BZN, 14 which corresponds also to a better ordered crystal structure. [4][5][6][7] In cubic pyrochlore BZN the Bi and Zn atoms in the A positions are disordered among six closely spaced equivalent sites and the OЈ atoms from the A 2 OЈ tetrahedral network among 12 sites, 4 while the Zn atoms prefer the B site to the A site.…”
Section: Introductionmentioning
confidence: 96%
“…The bulk structural and electronic properties of bismuth-based pyrochlore materials have been extensively studied mainly due to their general high dielectric constant and low dielectric loss, which are desirable properties in the field of electronics devising. , There is, however, a series of novel potential applications of this type of material, such as oxygen-evolution catalysis and visible-light photocatalysis, whose development largely depends on the knowledge of the surface chemistry. Pyrochlore bismuth iridates have been shown to have good activity and high stability for the oxygen evolution reaction, which is mediated by surface redox processes .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BZN films prepared by metal organic deposition (MOD) process [12][13][14], pulsed laser deposition (PLD) [15,16] and RF-magnetron sputtering [17][18][19] showed noticeable voltage-tunable dielectric properties. Recently, it was found that one of the most important factors for tunability is nonstoichiometry of the BZN films (especially Bi contents) when cubic BZN target is used [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that one of the most important factors for tunability is nonstoichiometry of the BZN films (especially Bi contents) when cubic BZN target is used [12,13]. In this work, the dielectric-tunable properties of BZN thin films by RF-magnetron sputtering using monoclinic BZN target were investigated in terms of nonstoichiometry.…”
Section: Introductionmentioning
confidence: 99%